Design of a preventive program to properly use personal protective equipment based on Standard-017-STPS-2008 - Duarte Beltrán , Elizabeth (2024)
The Social Security Institute in Mexico has recorded over 400,000 workplace accidents over the past decade. As a result, it has become necessary to design a preventive safety and health program in the laboratories of the Technological University of the Mixteca. This article presents a methodological proposal to address this necessity. Divided into six stages, it shows the following results: 40% suffered a superficial first-degree burn, 60% have hit or crushed their fingers and hands, 30% experienced eye injuries from particles causing irritation and inflammation, 70% have suffered from back and foot pain, 60% have had allergies, 50% have treated minor cuts, and 20% have developed occupational diseases. The study concludes that with technological advances in the workplace, smart equipment capable of eliminating risk should soon replace conventional personal protective equipment (PPE).